2014
DOI: 10.1371/journal.pone.0113935
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Linkage Scan Identifies Two Novel Genetic Loci for Coronary Artery Disease: In GeneQuest Families

Abstract: Coronary artery disease (CAD) is the leading cause of death worldwide. Recent genome-wide association studies (GWAS) identified >50 common variants associated with CAD or its complication myocardial infarction (MI), but collectively they account for <20% of heritability, generating a phenomena of “missing heritability”. Rare variants with large effects may account for a large portion of missing heritability. Genome-wide linkage studies of large families and follow-up fine mapping and deep sequencing are partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…More similar studies have also been performed in different populations, leading to the excavation of more CAD-related single nucleotide polymorphisms (SNPs) [4], [5]. As a result, population-based studies with thousands of patients and healthy controls included have identified more than 50 CAD-associated genetic loci in total [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…More similar studies have also been performed in different populations, leading to the excavation of more CAD-related single nucleotide polymorphisms (SNPs) [4], [5]. As a result, population-based studies with thousands of patients and healthy controls included have identified more than 50 CAD-associated genetic loci in total [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, the 3q29 and 9q22.33 CAD loci were identified by both GWLS with 24 large families (GeneQuest II) and by a similar analysis with 428 nuclear families in the GeneQuest population 40 . Our results also demonstrate that GWLA has a comparable power to GWAS.…”
Section: Discussionmentioning
confidence: 94%
“…Since then, over ten GWLAs, including our own studies, have identified additional genetic loci for CAD or MI, including 1p34–36,1q25, 2q14.3, 2q36–37.3, 2q13, 3q13, 5q31, 7p14, 8p22, 13q12–13,14q32.3, 15q26.3, 16p13, and 17p11.2–17q21 28 39 . Recently, we have completed a genome-wide linkage scan in a well characterized U.S GeneQuest cohort with 428 nuclear families and identified six novel CAD loci on chromosomes 3p25.1, 3p29, 9q22.3, 9p34.11, 17p12, and 21q22.3 40 . In contrast to aforementioned GWASs, the number of genetic loci identified by GWLA was much smaller and independent, suggesting that many linkage loci remain to be identified in new CAD or MI families 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The details of this diagnostic criteria and ascertainment of GeneQuest participants have been described by us previously (Guo et al, 2017, Gao et al, 2014, Shen et al, 2014). In brief, the presence or absence of CAD was evaluated according to a coronary angiography with a >70% stenosis, history of revascularization procedures, such as percutaneous coronary angioplasty (PCA) or coronary artery bypass (CABG), and previous diagnoses of MI as described (Guo et al, 2017, Gao et al, 2014, Shen et al, 2014). Patients with hypercholesterolemia, insulin-dependent diabetes, childhood hypertension, congenital heart disease, cardiomyopathy, valvular disease, and renal or hepatic disease were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%